Being women in Annie Ernaux’s Simple Passion novel - Tilbe, Ali (Border Crossing, 2020)
Being women in Annie Ernaux’s Simple Passion novel In Simple Passion, as in her other novels, the personal events that lead Ernaux’s life are narrated. Simple Passion, which carries some of the distinctions of the stylistic postmodernism short story narrative, is an autofictional self-narrative that offers readers such as “alienation to love, being a slave to passion and suffering emotional violence” in a very striking way. The narrative person narrates how her forbidden love for an Eastern stranger turns into a sensual passion and delusion, the phenomenon that such a human experience can find everyone, at any moment, anywhere, by passing the present through a social filter with a very clear simplicity and fearless past with the name of the singular first person “I”. This sickly state of passion takes over the narrative person’s mind, her life, dragging him toward spiritual and bodily exhaustion. He also wants to enter into a showdown with her family history, tell the woman who has submitted to society how she has gained a free female identity, and reverse the traditional patriarchal perception of women. In the study, we will try to explain the passionate captivity of a woman who refers to Simone de Beauvoir’s motto “One Is Not Born, But Rather Becomes, A Woman!” and who defies society by trying to exist with her self-identity in a spiral of emotional and sensual violence.